Impact of a patient-specific national programme aimed at increasing the use of emollient moisturisers to reduce the risk of skin tears: a longitudinal cohort study - Moffat, Anna K (BMJ Open, 2020)
OBJECTIVES: To evaluate the impact of a patient-specific national programme targeting older Australians and health professionals that aimed to increase use of emollient moisturisers to reduce to the risk of skin tears. DESIGN: A prospective cohort intervention. PARTICIPANTS: The intervention targeted 52 778 Australian Government’s Department of Veterans’ Affairs patients aged over 64 years who had risk factors for wound development, and their general practitioners (GPs) (n=14 178). OUTCOME MEASURES: An interrupted time series model compared the rate of dispensing of emollients in the targeted cohort before and up to 23 months after the intervention. Commitment questions were included in self-report forms. RESULTS: In the first month after the intervention, the rate of claims increased 6.3-fold (95% CI: 5.2 to 7.6, p<0.001) to 10 emollient dispensings per 1000 patients in the first month after the intervention. Overall, the intervention resulted in 10 905 additional patient-months of treatment. The increased rate of dispensing among patients who committed to talking to their GP about using an emollient was six times higher (rate ratio: 6.2, 95% CI: 4.4 to 8.7) than comparison groups. CONCLUSIONS: The intervention had a sustained effect over 23 months. Veterans who responded positively to commitment questions had higher uptake of emollients than those who did not.